give me answer of this question
tomorrow will be my paper please
urgent
Attachments:
![](https://hi-static.z-dn.net/files/d69/d206a7683b57d97cdf50ece352a559c8.jpg)
Answers
Answered by
1
now
(3√2/√6-√3)+(2√3/√6+2)-(4√3/√6-√2)
=(3√2/√3(√2-1))+(2√3/√2(√3+√2))-(4√3/√2(√3-1))
=(√6/√2-1)+(√6/√3+√2)-(2√6/√3-1)
=(√6(√2+1)/2-1)+(√6(√3-√2)/3-2)-(2√6(√3+1)/3-1)
=(√12+√6/1)+((√18-√12)/1)-(2√18+2√6/2)
=√12+√6+√18-√12-√18-√6
all get cancel answer is 0
gurreetpreet:
give simple way
Answered by
5
Answer:
hlo hupeet dear Ur so cute girl
Similar questions
Social Sciences,
1 year ago
English,
1 year ago
Science,
1 year ago
Computer Science,
1 year ago
Chemistry,
1 year ago